Sport mega-event fantasies to financialization: the case of Porto Maravilha - Bhimani, Zainab; De Lisio, Amanda (Frontiers in Sports and Active Living, 2023)
The paper will examine the legacies of urban legislation and construction within mega-event Rio de Janeiro on the financialization of housing, and in particular the use of the 2001 federal Statute of City and 1995 Strategic Plan for Rio de Janeiro, to create new possibilities for neoliberal-capitalist expansion, initially disguised as democratized access to land yet, in effect, further commoditized land (and associated real estate) into a form of “fictitious capital” (Aalbers 2017; Mosciaro & Pereira 2019; Mosciaro, Pereira & Aalbers 2019; Fernandez & Aalbers 2020). To do so, we follow Rolnik (2019) to the manner in which the focus on wealth distribution in urban legislation, propagated at the time of the sport mega-event in Brazil, was instead co-opted to endorse real estate speculation and the concentrate wealth within the domain of Brazilian corporate elite. In Brazilian and Latin American debate on large-scale urban reform, the coordination and collaboration between state and non-state authorities is historically associated with deepened socio-spatial inequities and the direct or indirect expulsion of low-income communities (Leal de Oliveira et al. 2020). The sport mega-event, and in particular urban reform initiated within Olympic host cities, coordinated the transference of wealth between state and non-state authorities as legally permitted via the Host City Contract and the flexibilization afforded through urban legislation. We are interested to trace different legislative strategies which proved to be conducive to a finance-led regime of accumulation within Porto Maravilha, a site of historic significance to the insertion of Brazil into global capitalism, particularly through the transatlantic slave trade, and more recently through financialized neoliberal urbanism.